Pomen in vpliv novih lingvističnih spoznanj Ferdinanda de Saussurja - Švajncer, Marija (Slavia Centralis, 2020)
THE IMPORTANCE AND INFLUENCE OF NEW LINGUISTIC COGNITION OF FERDINAND DE SAUSSURE The article deals with the importance and influence of new linguistic cognitions of Ferdinand de Saussure, one of the most important contemporary linguists and the beginner of structuralism. The subject of his investigations is the difference between language, speech and talking. He places the semiology into science. The article also deals with some cognition in the contemporary structuralistic philosophy inspired by de Saussure and his indirect influence on the development of Slovenian linguistics.
Keywords: language; system; semiology; marked; marker; sinchronia; structuralism